Capaian Hasil Merdeka Belajar Kampus Merdeka di Fakultas Psikologi dan Pendidikan Universitas Al Azhar Indonesia - Bahrul Ulum; Adiyo Roebianto; Helmi Triadi; Siti Zahraul Maftuhah (Universitas Al Azhar Indonesia, 2023)
The MBKM programs with the right to study three semesters outside the study program aim to improve the competence of soft skills and hard skills of graduates. However, this MBKM policy raises several new problems at the grassroots level as the executor of the policy, such as problems with conversion and achievement of Intended Learning Outcomes (CPL). The purpose of this study was to find out how the MBKM policy was implemented in the Faculty of Psychology and Education, Al Azhar Indonesia University, the opportunities and problems faced by the Psychology Faculty, Al Azhar University Indonesia, in implementing the MBKM policy. This study used a descriptive qualitative method with the aim of obtaining an overview and perception of the Faculty of Psychology and Education regarding the implementation of MBKM by means of data collection techniques by observation and interviews with all study programs under the auspices of the Faculty of Psychology and Education as well as documents related to MBKM. From the results of the study, it can be concluded that technically all structural officials support MBKM activities, but at the implementation stage they still face several obstacles, that are the need to adapt the curriculum to the MBKM, the difficulty of converting the MBKM program to study program courses, especially subjects that are expertise, as well as the student quota given by The Ministry of Education and Culture which is very low.Keywords - MBKM Curriculum, Opportunities and Problems, MBKM Program.